Cyclic arginine-glycine-aspartic acid-modified red blood cells for drug delivery: Synthesis and in vitro evaluation - Chen Wang; Min Wang; Yan Zhang; Hongxin Jia; Binbin Chen (Elsevier, 2022)
Red blood cells (RBCs) are an excellent choice for cell preparation research because of their biocompatibility, high drug loading, and long half-life. In this study, doxorubicin (DOX) was encapsulated with RBCs as the carrier. The biotin-avidin system binding principle was used to modify biotinylated cyclic arginine-glycine-aspartic acid (cRGD) onto RBC surfaces for accurate targeting, high drug loading, and sustained drug release. The RBC drug delivery system (DDS) was characterized, and the concentration of surface sulfur in the energy spectrum was 6.330%. The physical and chemical properties of RBC DDS were as follows: drug content, 0.857 mg/mL; particle size, 3339 nm; potential value, −12.5 mV; and cumulative release rate, 81.35%. There was no significant change in RBC morphology for up to seven days. The results of the targeting and cytotoxicity studies of RBC DDS showed that many RBCs covered the surfaces of U251 cells, and the fluorescence intensity was higher than that of MCF-7 cells. The IC50 value of unmodified drug-loaded RBCs was 2.5 times higher than that of targeted modified drug-loaded RBCs, indicating that the targeting of cancer cells produced satisfactory inhibition. This study confirms that the RBC DDS has the characteristics of accurate targeting, high drug loading, and slow drug release, which increases its likelihood of becoming a clinical cancer treatment in the future.